The Efficacy of Topical Ointments in the Treatment of Common Cutaneous Warts: A Meta-Analytical Study - Dr. Rajdeep Sonkar; Dr Pranab kumar Chakraborty; Dr. Anil Aggarwal; Dr. Narendra Narayan Chattopadhyaya; Dr. Bimlendu Kumar Roy (The Bioscan, 2026)
Among skin warts, Cutaneous Warts, caused by the human papillomavirus (HPV), are one of the most common dermatological problems worldwide. About 7-12% of people suffer from HPV worldwide, and many times they visit their primary health care providers for diagnosis and treatment. There are various topical drugs available in the market; however, the treatment response varies a lot due to different efficacies, reoccurrences, and side effects. In order to compare the efficacies and safety of different topical treatments used for common, plantar, and flat warts, a meta-analysis has been performed. A systematic literature search was conducted, and studies reporting wart clearance rates, recurrence, or adverse effects associated with topical agents, including salicylic acid (SA), imiquimod, 5-fluorouracil (5-FU), cantharidin, formic acid, podophyllotoxin, cidofovir, and occlusive therapy, were included. The results showed that salicylic acid demonstrated the best pooled clearance rates (60- 75%; OR = 4.1 vs placebo), cantharidin ranked second (70-85%), followed by imiquimod (50-75%). 5- Fluorouracil was found to have moderate efficacy (55-65%). The recurrence rate was lower in imiquimod (10-20%) and cantharidin (12-18%) treatments, while side effects were relatively mild. There was some heterogeneity among the included studies (I² = 52-64%). On balance, salicylic acid will remain the treatment of choice due to its well-established profile, availability, and low cost. Combination and/or sequential therapy could prove effective in resistant cases, but individualized treatment approaches as well as additional high-quality RCTs are required.